2019
DOI: 10.3389/fimmu.2019.00759
|View full text |Cite
|
Sign up to set email alerts
|

ALCAM Mediates DC Migration Through Afferent Lymphatics and Promotes Allospecific Immune Reactions

Abstract: Activated leukocyte cell adhesion molecule (ALCAM, CD166) is a cell adhesion molecule of the immunoglobulin superfamily and has been implicated in diverse pathophysiological processes including T cell activation, leukocyte trafficking, and (lymph)angiogenesis. However, exploring the therapeutic potential of ALCAM blockade in immune-mediated inflammatory disorders has been difficult due to the lack of antibodies with blocking activity toward murine ALCAM. In this study, we identified and characterized a monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…Control groups were either treated with KSF-Fc, i.e. an Fc-fusion of a single-chain variable fragment (scFv) directed against hen egg lysozyme 37 , or dexamethasone (i.e. a corticosteroid).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control groups were either treated with KSF-Fc, i.e. an Fc-fusion of a single-chain variable fragment (scFv) directed against hen egg lysozyme 37 , or dexamethasone (i.e. a corticosteroid).…”
Section: Resultsmentioning
confidence: 99%
“…Mice were treated i.p. with 37 μg mIL-7-Fc or corresponding control fusion protein (KSF-Fc; non-specific single chain Fv antibody fragment against hen egg lysozyme 53 , fused to an IgG1 Fc fragment, and produced in our lab 37 , or 400 μg anti-IL-7α blocking antibody (clone A7R34, Bioexcell, West Lebanon, USA) or corresponding IgG control (clone 2A3, Bioexcell) every other day. I.p.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the control-treated mice, Treg frequencies in dLNs were significantly increased, indicating tolerance-inducing conditions [155]. Surprisingly, the beneficial effect of ALCAM blockade on corneal transplant survival could not be attributed to impaired lymph-or hemangiogenesis, since no difference was detected in vessel ingrowth into the cornea between treated and control mice.…”
Section: Activated Leukocyte Cell Adhesion Molecule (Alcam)mentioning
confidence: 87%
“…Focusing on DCs, blockade of ALCAM reduced the adhesion of DCs to LEC monolayers [152]. Studies on in vitro-cultured human skin biopsies showed reduced emigration from DCs when ALCAM was blocked [155]. However, its confirmed role in the organization and function of lymphatic vessels, together with an indicated effect on DC migration, suggests therapeutic potential.…”
Section: Activated Leukocyte Cell Adhesion Molecule (Alcam)mentioning
confidence: 99%
“…(S1pr1). Alcam is required for cDC migration via afferent lymphatics, and its blockade through high-affinity antibodies induces cDC retention and alleviates cDC-induced allogenic responses (52). Further, since migratory cDCs can activate T cells through a stable immunological synapse (53), the upregulated Alcam level may explain the increase of T EM cells vs. naïve T-cell populations following pre-treatment with tRA.…”
Section: Enhancement Of Systemic Inflammation By Tra Pre-treatment Inmentioning
confidence: 99%